Pemikiran Kesederhanaan Dalam Isu-Isu Akidah Menurut Sheikh Zainal Abidin al-Fatani - Abd. Latif, Faizuri; Abdul Hamid, Faisal @ Ahmad Faisal (Afkar: Jurnal Akidah dan Pemikiran Islam, 2014)
Moderate thinking has been practiced by the Malay scholars in their writings because moderation plays an important role in fostering the spirit of love and tolerance in humans. Moreover, it is also one of the main demands of Islam. Without understanding this issue and realize the importance of moderate thinking will lead an individual to be extreme and difficult to accept others views. Thus, Malay scholars whose role is to bring people in the archipelago together has taken the initiative in applying moderate thinking in the issues of `aqidah that led to discords among Muslims. For them there is no best way to defuse arguments occured unless each individual is ready to tolerate others views. This article discusses the concept of moderation in `aqidah based on the ideas of Malay scholar Sheikh Zainal Abidin al-Fatani or ‘Tuan Minal’ anchored in his work `Aqidah al-Najin, as he is seen to put forwards this concept which is suitable and can be practiced by his current and future communities.